Tingkat Percaya Diri Atlet Cabang Olahraga Individual dan Beregu - Rangga Ahmad Hamdani; Hadi Sartono (Jurnal Kepelatihan Olahraga, 2021)
This study discusses about the level of self-confidence in athletes. Self-confidence in every sport must be possessed by every athlete, especially in individual and team sports. The purpose of this study is to determine the level of self-confidence of athletes in individual and team sports. The method used in this research is quantitative descriptive method. The sample that researcher used was 30 people, each of 15 individual athletes and 15 team athletes who joined UKM at UPI. The approach used is a random sampling approach. The instrument used was a confident questionnaire. The result of this study indicated that the level of self-confidence of individual sports athlete is greater than team sports athlete. It can be concluded that the level of self-confidence in individual sports athlete is greater than the level of self-confidence in team sports athlete. The researcher advise to individual sports athlete and team sports athlete to maintain and to increase their level of self-confidence.